Syndromes associated with mitochondrial DNA depletion - Nogueira, Célia (2014)
Mitochondrial dysfunction accounts for a large group of inherited metabolic disorders most of which are due to a dysfunctional mitochondrial respiratory chain (MRC) and, consequently, deficient energy production. MRC function depends on the coordinated expression of both nuclear (nDNA) and mitochondrial (mtDNA) genomes. Thus, mitochondrial diseases can be caused by genetic defects in either the mitochondrial or the nuclear genome, or in the cross-talk between the two. This impaired cross-talk gives rise to so-called nuclear-mitochondrial intergenomic communication disorders, which result in loss or instability of the mitochondrial genome and, in turn, impaired maintenance of qualitative and quantitative mtDNA integrity. In children, most MRC disorders are associated with nuclear gene defects rather than alterations in the mtDNA itself.The mitochondrial DNA depletion syndromes (MDSs) are a clinically heterogeneous group of disorders with an autosomal recessive pattern of transmission that have onset in infancy or early childhood and are characterized by a reduced number of copies of mtDNA in affected tissues and organs. The MDSs can be divided into least four clinical presentations: hepatocerebral, myopathic, encephalomyopathic and neurogastrointestinal. The focus of this review is to offer an overview of these syndromes, listing the clinical phenotypes, together with their relative frequency, mutational spectrum, and possible insights for improving diagnostic strategies.